AB1180 The influence of mechanical stress on the hands on ultrasound results: a prospective study with volleyball players (US-VOLLEY) – preliminary data. (12th June 2018) - Scheicht, D.; Zeglam, S.; Frechen, S.; Strunk, J.
Abstract : Background: Various imaging studies have found an influence of physical exercise on joint and tendon pathology in ultrasound. It is not clear 1 how specific grey scale and power Doppler changes are in a context of mechanical stress and 2 if a distinction to findings in acute arthritis exists. Objectives: To examine via grey scale and power Doppler ultrasound the acute physiological effects of increased physical stress on the fingers and wrists and their surrounding structures through volleyball training in amateur healthy subjects as a reference to the known pathological findings (effusion, increased perfusion) in acute arthritis. Methods: Examination of 18 healthy amateur volleyball players via musculoskeletal ultrasound before and directly after their routine volleyball practice. Ultrasound assessment included a grey scale and power Doppler examination of the dominant hand (longitudinal planes of the dorsal wrist and dorsal and palmar planes of MCP II-III and PIP II-III joints). Findings were graded semi-quantitatively from 0 to 3 both in grey scale (effusion) and power Doppler (perfusion). The results of the joint assessment were aggregated in a composite index for grey scale and power Doppler (range 0–54 points). All ultrasound images were graded by two independent raters who were blinded to image acquisition. Results: Volleyball training showed statistically significant effects in the composite index for grey scale and power Doppler scores (p=0.004). 16 of 18 players showed a change in their composite index with a median change of 1 and a maximum change of 3 points. Subanalysis revealed that changes were related to grey scale exclusively, with no statistical difference in power Doppler scores. Conclusions: The results of our study suggest that mechanical stress on the hands leads to changes in grey scale ultrasound in healthy subjects in at least one joint. However, the composite index for changes in grey scale and power Doppler changed 3 points at the most in one subject over various joints. To add, no changes in power Doppler score were observed. While changes in grey scale ultrasound appear to be minor, power Doppler ultrasound appears to be a more robust method and less prone to environmental factors. Power Doppler appears to be able to discriminate between physiological changes due to mechanical stress and acute arthritis and thus, is highly specific. Disclosure of Interest: None declared